The impact of e-marketing on leisure tourism in the Kingdom of Saudi Arabia: A field study - Arous, Jamel Ali; Louail, Bilal; Hima, Nadya Ali; Tayeb, Mesud Essa (Journal of Tourism Management Research, 2024)
This research examined the impact of electronic marketing on tourists’ preferences by conducting a field study on a sample of citizens and residents in the northern border region of the Kingdom of Saudi Arabia. The study aims to understand the relationship between e-marketing campaigns through three variables: digital presence and online content, interaction of bloggers and influencers, social networking sites, online presence and content, and their impact on leisure tourism, through visitor satisfaction and personal experience as an intermediary variable, and how that affects visitors’ satisfaction and users’ decisions regarding their decisions in choosing recreational tourist destinations in the Kingdom of Saudi Arabia. The research aims to shed light on the role of electronic marketing in encouraging leisure tourism and identify the factors influencing tourist decisions in this context. This study utilized surveys conducted with users, totaling 756 participants. We used the quantitative method in the process of collecting and analyzing data from the study to identify the factors influencing users’ responses to such information. The data analysis process relied on structural equation modeling using both Amos program and the SPSS program. The study concluded that the results indicate a relationship and influence between electronic marketing campaigns and their variables, digital presence, and online content, social media sites, bloggers, and influencers interact, through visitor satisfaction and user experience, which leads to an increase in tourists’ preference for leisure tourism in the Kingdom of Saudi Arabia.